2021
DOI: 10.1093/neuonc/noab081
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide-induced hypermutation is associated with distant recurrence and reduced survival after high-grade transformation of low-grade IDH-mutant gliomas

Abstract: Background Chemotherapy improves overall survival after surgery and radiotherapy for newly diagnosed high-risk IDH-mutant low-grade gliomas, but a proportion of patients treated with temozolomide (TMZ) will develop recurrent tumors with TMZ-induced hypermutation. We aimed to determine the prevalence of TMZ-induced hypermutation at recurrence and prognostic implications. Methods We sequenced recurrent tumors from 82 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Recent studies have warned that temozolomide treatment of LGG induces hypermutation, which may drive malignant progression. 53 , 54 ) Tom et al 11 ) reported adjuvant temozolomide monotherapy as the only modifiable risk factor for malignant transformation among adult LGG cases. Aihara et al 55 ) indicated that malignancies are rarely promoted by additionally acquired mutations or genomic aberrations at recurrence of oligodendrogliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have warned that temozolomide treatment of LGG induces hypermutation, which may drive malignant progression. 53 , 54 ) Tom et al 11 ) reported adjuvant temozolomide monotherapy as the only modifiable risk factor for malignant transformation among adult LGG cases. Aihara et al 55 ) indicated that malignancies are rarely promoted by additionally acquired mutations or genomic aberrations at recurrence of oligodendrogliomas.…”
Section: Discussionmentioning
confidence: 99%
“…GBM is a progressive debilitating cancer in the central nervous system (CNS) and takes up over 50% of brain-related carcinomas in adults [ 36 ], which is associated with a very poor prognosis [ 29 , 37 ]. Despite the application of combined radiotherapy and chemotherapy with TMZ after optimal surgery, most patients eventually develop TMZ resistance and suffer from the malignant relapse of aggressive tumors [ 38–40 ].Recent studies revealed that RUNX1 and miRNAs are implicated in the development of resistant phenotype of TMZ in GBM [ 41–43 ]. Here, the present study identified miR-128-3p as a negative regulator of RUNX1 and validated their functional interaction in TMZ sensitivity of GBM cells, suggesting that miR-128-3p/RUNX1 axis could serve as a potential therapeutic target in TMZ-resistant GBM.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that irradiation could have allowed for the evolution of MGMT -unmethylated tumor cells, which “escaped” and migrated to the other hemisphere, or perhaps that those cells had already infiltrated to the corpus callosum and out of the radiation field prior to the initial irradiation, providing an explanation for the development of temozolomide resistance seen at recurrence. It is also possible that the temozolomide treatment itself promoted extensive mutation, as recently demonstrated in IDH-mutant low-grade gliomas [ 44 ], promoting the escape of resistant clones toward the contralateral hemisphere. More importantly, our data also suggest that changing molecular features (including MGMT promoter methylation and other key markers of aggressiveness and treatment responsiveness in diffuse gliomas) may be missed in the routine analysis of single biopsy or resection samples and that whole-genome methylation profiling and copy number profiling in multiple samples may provide useful information in the case of tumor recurrence to identify potentially useful changing molecular milieu.…”
Section: Discussionmentioning
confidence: 99%